Regulation of glucagon release in mouse -cells by KATP channels and inactivation of TTX-sensitive Na+ channels. - Göpel, S; Kanno, T; Barg, S; Weng, X; Gromada, J; Rorsman, P (2000)
The perforated patch whole-cell configuration of the patch-clamp technique was applied to superficial glucagon-secreting alpha-cells in intact mouse pancreatic islets. alpha-cells were distinguished from the beta- and delta-cells by the presence of a large TTX-blockable Na+ current, a TEA-resistant transient K+ current sensitive to 4-AP (A-current) and the presence of two kinetically separable Ca2+ current components corresponding to low- (T-type) and high-threshold (L-type) Ca2+ channels. The T-type Ca2+, Na+ and A-currents were subject to steady-state voltage-dependent inactivation, which was half-maximal at -45, -47 and -68 mV, respectively. Pancreatic alpha-cells were equipped with tolbutamide-sensitive, ATP-regulated K+ (KATP) channels. Addition of tolbutamide (0.1 mM) evoked a brief period of electrical activity followed by a depolarisation to a plateau of -30 mV with no regenerative electrical activity. Glucagon secretion in the absence of glucose was strongly inhibited by TTX, nifedipine and tolbutamide. When diazoxide was added in the presence of 10 mM glucose, concentrations up to 2 microM stimulated glucagon secretion to the same extent as removal of glucose. We conclude that electrical activity and secretion in the alpha-cells is dependent on the generation of Na+-dependent action potentials. Glucagon secretion depends on low activity of KATP channels to keep the membrane potential sufficiently negative to prevent voltage-dependent inactivation of voltage-gated membrane currents. Glucose may inhibit glucagon release by depolarising the alpha-cell with resultant inactivation of the ion channels participating in action potential generation.